Influencing factors of customer loyalty in the malaysian airline industry using structural equation modelling (SEM) / Haslinda Ab Malek ... [et al.] - Ab Malek, Haslinda; Haris, Nurhamiza; Wendri, Siti Sara; Syed Faisal, Sharifah Najihah; Ab Malek, Isnewati (Universiti Teknologi MARA, Kedah, 2022)
The airline industry is considered one of the commanding heights of the global economy that facilitates international economic exchanges. Many airline incidents have severely affected the financial and reputation of airline companies. Customers begin to have negative perceptions and lost their trust towards the organizations involved. Therefore, this study was conducted to identify the most influencing factors that contribute to customer loyalty in the airline industry. 301 respondents have been selected randomly to participate in this research. The data was analyzed using Structural Equation Modelling and the results yield that commitment was found to be the most influencing factor for customer loyalty. This research benefits airline organizations specifically. From this research, the organization should have a deeper insight and better understanding of customer loyalty. Hence, this research should be able to aid airline marketers to plan better strategies to increase their revenues and retain or gain the customer.